The Potential of Black Cumin (Nigella sativa) as an Immunostimulant in Aquaculture (Review) - Muahiddah, Nuri; Diniariwisan, Damai (Jurnal Biologi Tropis, 2024)
Research on the use of black cumin (Nigella sativa) as an immunostimulant in aquaculture has shown interesting potential. In this review, we explore the potential of black cumin as an immunostimulant in aquatic animals. Based on a recent literature review, we highlight the positive effects of black cumin extract in enhancing immune responses in aquatic organisms. The active compounds in black cumin, such as thymoquinone and α-hederin, are thought to have the ability to stimulate the immune system, increase cytokine production, and increase phagocytic activity. Implications of using black cumin in aquaculture include the potential to improve the health and productivity of aquatic animals. However, challenges such as dose optimization, effectiveness in various aquatic species, and environmental risk management need to be addressed. Suggestions for further research include more in-depth studies of the mechanism of action, clinical trials on various aquatic species, as well as environmental impact assessments. With a careful and coordinated approach, the use of black cumin as an immunostimulant has the potential to increase sustainability and productivity in aquaculture practices.